Original paper Analysis of the correlation between level of anxiety, intensity of depression and bronchial asthma control - Pietras, Tadeusz; Panek, Michał; Witusik, Andrzej; Wujcik, Radosław; Szemraj, Janusz; Górski, Paweł; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Somatic and mental disorders are present in patients suffering from obstructive diseases such as bronchial asthma. Physical complaints can induce anxiety and mood disturbances that correlate with worsened quality of life and are considered as very important factors in prognosis of bronchial asthma status. Depression and dyspnoea modify the level of asthma severity according to GINA, the result of the Asthma Control Test, and sensitivity to asthma treatment. Currently, researchers more often than before emphasize the clear role of psychopathological factors in the course of bronchial asthma. Aim : To assess the correlation between the score in the Asthma Control Test (ACT), in patients with bronchial asthma who were well, partially and poorly controlled, and psychopathological factors. Material and methods : The study enrolled 167 patients diagnosed with bronchial asthma and 178 healthy people, as the control group. Structuralized anamnesis was obtained and spirometry was performed in compliance with the standards set by the Polish Respiratory Society. Respiratory disturbances and their severity were evaluated according to the GINA Report. All the patients were assessed using the ACT, Beck Depression Inventory and Spielberger State-Trait Anxiety Inventory (STAI). Multiple positive correlations were found between psychopathological factors and the result of the ACT in the group of bronchial asthma patients versus controls. Results : According to GINA, mild asthma was diagnosed in 24 patients, moderate in 76, and severe disease in 67. Hundred three patients were assessed as poorly controlled (62.2%), 60 partially controlled (35.5%) and 4 well controlled (2.3%). The intensity of depression and the level of anxiety modified the level of asthma severity according to GINA ( p < 0.05). Depression, anxiety-state and anxiety-trait modified the level of asthma control in the Asthma Control Test (ACT™) ( p < 0.05). Conclusions : A positive correlation between psychopathological variables and the result of the ACT was observed in the studied group of patients with bronchial asthma versus the control group.